Game Model on Income Distribution for Expressway Network Tolling - Yinggui Zhang; Mengjun Wang; Dingyou Lei; Hanfen Hu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Reasonable income distribution for expressway network tolling plays a positive role in attracting investors and social funds to accelerate expressway construction and development. Influence factors of the income distribution problem for expressway network tolling were analyzed and the income distribution process of expressway network tolling was further viewed as a bargaining game in the paper. Then, an income distribution model based on bargaining game for expressway network tolling was proposed to increase the return rates for expressway investors and further mobilize their enthusiasm for expressway investment. Finally, we proposed one numerical example for the income distribution problem with the help of such game model. Also, The results demonstrated that the precedence investors with much more optimistic attitudes to expressway investment could share much more from expressway network tolling, and also the traffic volume distribution compensation from the government in an opened or hidden way further could enhance investors’ enthusiasm for the expressway investment with certain low discount rates. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2541